Design & analysis of solid rocket using open rocket software. (2022) - Rohini, D.; Sasikumar, C.; Samiyappan, P.; Dakshinamurthy, B.; Koppula, Neeraja
Abstract: Model rockets are small sized rockets which are used to understand how a full-sized rocket along with its engine works. In this project design, analyze, fabrication and testing of a Solid Propellant Rocket Model carried out. Solid rocket motors (or SRMs) are systems with minimal moving parts. An input is amplified to the igniter, which produces hot gases. The main propellant grain is ignited by hot gases. Because the propellant comprises both fuel and oxidizer, this equipment are capable of operating in the vacuum of space. The high thermal energy of the combustion gases is transferred to kinetic energy in the exhaust, resulting in thrust. The body of the rocket designed using Open Rocket software and analyzed its flight characteristics using the same software. In this research work Dextrose used as the fuel and Potassium Nitrate used as the Oxidizer and made the solid propellant for the rocket. After that the motor is tested using a thrust stand. The body of the rocket fabricated and assembled it with the motor. Finally, tested the rocket by launching it using a launch pad.